Dampak People Pleaser Terhadap Kesehatan Mental Pada Mahasiswa Prodi Bimbingan dan Konseling Islam Fakultas Dakwah dan Komunikasi UIN Ar-Raniry Banda Aceh - Fadhilla Fadhilla; Mira Fauziah; M.Yusuf MY (Ameena Journal, 2026)
People pleaser behaviour among students is reflected in the tendency to place others’ needs and expectations above personal interests, which can be seen through difficulties in refusing requests, fear of disappointing others, and a strong desire for social approval. This phenomenon may negatively affect students’ mental health. This study aims to examine the factors contributing to the development of people pleaser behaviour and its impact on the mental health of students in the Islamic Guidance and Counseling Study Program, Faculty of Da'wah and Communication, UIN Ar-Raniry Banda Aceh. This study employed a qualitative approach with a descriptive case study design. Ten students were selected using purposive sampling based on initial screening through Google Forms. Data were collected through observation, semi-structured interviews, and documentation, and analysed using the Miles and Huberman interactive model. The findings indicate that people pleaser behaviour is influenced by parenting experiences, social acceptance needs, and peer attachment, particularly the alienation aspect. The behaviour contributes to overthinking, anxiety, guilt, and emotional exhaustion, while self-boundaries help reduce its negative effects.